Insights into unit cell size effect on mechanical responses and energy absorption capability of titanium graded porous structures manufactured by laser powder bed fusion. (September 2020) - Yang, Lei; Han, Changjun; Wu, Hongzhi; Hao, Liang; Wei, Qingsong; Yan, Chunze; Shi, Yusheng
Abstract: Schwartz diamond graded porous structures (SDGPSs), constructed by a triply-periodic-minimal-surface diamond unit cell topology, were developed with various unit cell sizes and printed by laser powder bed fusion (LPBF) from a commercially pure titanium powder for bone implant applications. The effect of unit cell size on the printability, strut dimensions, stress and strain distributions, mechanical properties and energy absorption capability of SDGPSs was investigated. The results indicate the good printability of SDGPSs via LPBF with multiple unit cell sizes from 3.5 mm to 5.5 mm through the three-dimensional reconstruction from micro-computed tomography. The unit cell size plays a critical role in both strut diameters and specific surface areas of SDGPSs. An increase in the unit cell size leads to a reduction in the experimental Young's modulus from 673.08 MPa to 518.71 MPa and compressive yield strength from 11.43 MPa to 7.73 MPa. The mechanical properties of LPBF-printed SDGPSs are higher than those predicted by the finite element method, which is attributed to the higher volume fractions of the printed SDGPSs than the designed values. Furthermore, a rise in unit cell size leads to the decrease of energy absorption capability from 6.06 MJ/mm 3 to 4.32 MJ/mm 3 and exhibits little influence on the absorption efficiency. These findings provide a good understanding and guidance to the optimization on the unit cell size of functionally graded porous structures for desirable properties.